І. Нечуй-Левицький та Емський указ - Терещенко, Олександр Миколайович; Tereschenko, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті здійснено спробу висвітлити вплив Емського указу на національно-культурну діяльність І. Нечуя-Левицького, проаналізовано його ставлення до цензури в Російській імперії.An attempt to highlight the impact Ems decree on the socio-political and ethno-cultural activities I. Nechuy-Levitsky, analyzed the attitude of the writer to the censorship policy of the Russian autocracy, characterized journalistic legacy of John S. devoted to the problem of russification of Ukrainian lands, highlighted the impact of censorship on the development work of the artist. We consider a set of the special law enforcement bodies of the Russian Empire which contain findings censors on printing works I. Nechuy-Levitsky.
I. Nechuy-Levitsky and Ems Decree
Keywords: Емський указ; Київська громада (Громада); культорологічні трактати; русифікація; цензура; Ems decree community; a cultural treatises; Russification; censorship